A rare case of hepatic vein puncture during attempted pericardiocentesis mimicking right atrium perforation - Upadhyay, Amar Nath; Kumar, Barun (International Journal of Research in Medical Sciences, 2022)
Emergency pericardiocentesis done for hemodynamically significant cardiac tamponad is associated with rare but life-threatening complications including cardiac chamber perforation. Echocardiography is the usual tool to diagnose procedural complications of pericardiocentesis. We are reporting a case of attempted pericardiocentesis where apparent cardiac chamber perforation by saline contrast echo turned out to be an inconsequential hepatic vein puncture.